Graduating nursing students' user experiences of the immersive virtual reality simulation in learning - A qualitative descriptive study - Henna Mäkinen; Elina Haavisto; Sara Havola; Jaana‐Maija Koivisto (Wiley, 2023)
Abstract Aim To describe nursing students' user experiences' (UX) regarding highly immersive virtual reality (VR) simulation with head mounted display used for learning. Design Qualitative descriptive study. Methods Graduating nursing students (n = 41). Individual interviews were held right after VR simulation. The usability was assessed using System Usability Scale (SUS). Results User experiences emphasized three themes about the highly immersive VR simulation: nursing care in the immersive VR simulation, technology in the immersive VR simulation, and learning nursing in the immersive VR simulation. Usability was evaluated as fair (SUS score 62.3 out of 100). Scores revealed that the VR simulation was easy to use. The support of a technical person was highlighted. Conclusions This study supports strongly the use of highly immersive VR simulation for nursing education. VR simulations should replicate the most authentic nursing care. Technical assistance is crucial when adopting new technologies in education. The results highlighted the importance of UX in an education context.